THE EFFECT OF DIFFERENT RATIO OF BACTERIA (LACTOBACILLUS BULGARICUS + STREPTOCOCCUS THERMOPHILUS AND BIFIDOBACTERUM LONGUM. ATCC15707) ON CHARACTERISTICS OF YOGURT AT DIFFERENT STORAGE PERIOD - M Sabbah; anang legowo; Y Pramono (Jurnal Aplikasi Teknologi Pangan, 2012)
The main purpose of this research is to provide information about the effect of Bifidobacterium longum ATCC15707 on the characteristics of yogurt during different of storage period. The B.longum was obtained from Laboratory of Food and Nutrition Collection Culture Gadjah Mada University and a S.thermophillus + L.bulgaricus (1:1) was obtained from a commercial yogurt (Milkuat). This research was performed in Laboratory of Animal Science and Dairy Milk Processing Industry, Gadjah Mada University, used 8 L fresh milk cow, yogurt sample were stored at 4 ºC for 28 days.  Research using Completely Randomized Design with Factorial pattern A x B (4 x 2). Factor A is the ration between yogurt starter ST+Lb and BL (T1 is control 4% from yogurt starter, T2 1:3 (v/v), T3 2:2 (v/v), T4 3:1(v/v)). Factor B is the storage period (1 and 21 days) for chemical, physical and organoleptic analyses and (1, 14, 21 and 28) for microbial. Parameters measured are microbiology (total lactic acid bacteria), chemistry (acidity, pH, total solids, fat, protein and lactose), physical (viscosity) and organoleptic quality (color, texture, taste, performance, sweetness, acidity, bitterness and rancidity). If there is a real effect of treatment was followed by Duncan Multiple Test and LSD test for organoleptic quality. Microbial counts were log transformed and statistically evaluated. The result indicated that the yogurt produce with 3% (S.thermophillus and L. delbrueckii subsp. bulgaricus) and 1% B.longum ATCC15707 during storage period (1 and 21 days) at 4 ºC effected significantly to increase acidity and total solid of yogurt more than other treatment, decrease pH value significantly different. Also this ratio between starter bacteria obtained the high score in the taste and texture from the panelists.